HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KONFLIK PERAN GANDA PADA GURU PAUD WANITA DI KECAMATAN TAMPAN KOTA PEKANBARU - Simamora, Wilda Sari; Risma, Devi; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the teacher of women who have not been able to manage their emotional intelligence so that many dual role conflicts occur. High emotional intelligence has a positive influence on multiple role conflicts experienced by female teachers. Without high emotional intelligence, it will be difficult for female teachers to be able to reduce multiple role conflicts experienced. This study aims to determine whether there is a relationship between emotional intelligence and dual role conflict in female teacher teachers in the Handsome District of Pekanbaru City. This research is a quantitative research with a type of correlation research. Sampling technique used in this study is Sample Random Sampling with 75 subjects. Data collection techniques used were questionnaires, emotional intelligence questionnaires consisting of 25 items with reliability of 0.883 and multiple role conflict questionnaires consisting of 34 items with a reliability of 0.935 prepared by the author. Data analysis techniques were carried out using Pearson Product moment correlation statistics. Based on the results of the hypothesis test is known from the correlation coefficient value of rxy = -0.230 with a significance of 0.047 <0.05. Thus it can be concluded that there is a relationship between emotional intelligence and multiple role conflict. The level of relationship is included in the low category with the determinant coefficient value produced is 5.29% so it can be seen that emotional intelligence contributes 5.29% to multiple role conflicts. Keyword: emotional intelligence, work-family conflict